1966
DOI: 10.6028/jres.070c.022
|View full text |Cite
|
Sign up to set email alerts
|

Deflection of centrally loaded thin circular elastic plates on equally spaced point supports

Abstract: (Jul y 8, ] 966)Bassali 's ge ne ral th eo ry fo r the fl exure of th e thin c irc ul a r elastic pl a te suppo rted a t a n a rbitrary numbe r of points a nd subj ec ted to tran sverse load ove r a n ecce ntri c circle is spec ialized to th e case of a centrally load ed pla te s upporte d at points equally s paced on a c ircle co nce ntri c with th e ce nte r. Simplified me thod s fo r approximating th e res ults predi cted by th e more complic ated theo re ti cal ex· pressions for defl ec ti o n are prese nt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

1967
1967
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
3
7
0
Order By: Relevance
“…The test results presented herein were obtained from retesting specimen A of a previous investigation [3]. Since the specimens, materials, and test methods were fully described in the previous paper, it suffices here to indicate that the dead load method of testing was used, and the tangential strains were measured along the support circle (t = 0.976 and m = 3) by means of foil type electrical resistance strain gages having a gage length of 1/8 in.…”
Section: Comparison Of Theoretical and Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The test results presented herein were obtained from retesting specimen A of a previous investigation [3]. Since the specimens, materials, and test methods were fully described in the previous paper, it suffices here to indicate that the dead load method of testing was used, and the tangential strains were measured along the support circle (t = 0.976 and m = 3) by means of foil type electrical resistance strain gages having a gage length of 1/8 in.…”
Section: Comparison Of Theoretical and Experimental Resultsmentioning
confidence: 99%
“…In a previous paper [3] a special application of this more general solution was used to obtain a method of determining the deflection of a plate subjected to symmetrical bending with the load uniformly distributed over region 1. A c9mparison of theoretical and experimental results indicated that the theory adequately predicted the deflection of the plates over the range of geometries tested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical expressions for the deflection of a plate were obtained from Bassali's work [2) and a previous specialization [1] of his work whic h dealt with the de fl ection of centrally loaded thin c ircular elastic plates on equally spaced point supports. The previous case considered that the point supports were located along a co ncentric circle outside of the central loaded area (in Region 2).…”
Section: Deflection Of the Circular Platementioning
confidence: 99%
“…Figure 1 shows the concentric arrangement of the circular plate and defines Regions 1 and 2. Previously developed [1 , 2] general expressions pertaining to symm e tri cal bending are presented here as eqs (1) to (7)_ For the case considered here, the d evelopm e nt follows the same general reasoning_ The deflections of the plate in Regions 1 and 2 a re re prese nted by Po [ 1 11/ Rs (1)…”
Section: Deflection Of the Circular Platementioning
confidence: 99%